1989
DOI: 10.1107/s0108768189000777
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of 1-methyluracil from neutron diffraction at 15, 60 and 123 K

Abstract: The crystal structure of 1-methylpyrimidine-2,4-dione (1-methyluracil, C5H6N202) has been determined at 15, 60 and 123 K from neutron diffraction data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 7 publications
3
31
0
Order By: Relevance
“…7, N3: 0, N1: Ϫ1) together with simulated plots obtained with different NH values, for the NH values indicated. It is seen that the fit between the experimental and simulated plots is reasonably good with NH ϭ 15°and this value is also consistent with the NC values given in Table 1 as the N-C and N-H vectors, which are in the molecular plane, include an angle of ϳ115° (35). In view of this we did not consider the 1D data in the final estimation of NH and NH values (Table 1).…”
Section: Figsupporting
confidence: 82%
See 1 more Smart Citation
“…7, N3: 0, N1: Ϫ1) together with simulated plots obtained with different NH values, for the NH values indicated. It is seen that the fit between the experimental and simulated plots is reasonably good with NH ϭ 15°and this value is also consistent with the NC values given in Table 1 as the N-C and N-H vectors, which are in the molecular plane, include an angle of ϳ115° (35). In view of this we did not consider the 1D data in the final estimation of NH and NH values (Table 1).…”
Section: Figsupporting
confidence: 82%
“…In view of this we did not consider the 1D data in the final estimation of NH and NH values (Table 1). For ( NC , NC ) values of N1:(92, 100) and N3:(132, 88) degrees and making use of the H-N-C angle of ϳ115°given in the literature (35), one finds the corresponding ( NH , NH ) values to be (15,90) and (15, Ϫ80) degrees. For these values of the angles, the orientation of the 15 N CS tensor in uracil is seen to be as depicted in Fig.…”
Section: Figmentioning
confidence: 99%
“…Columns (I), (II) and (IIv) give present results from refinements based on X-ray diffraction data. Column MC gives results of McMullan & Craven (1989) based on neutron diffraction data collected at 123 K.…”
Section: Discussionmentioning
confidence: 99%
“…We now report a study of l-methyluracil ( & Rich (1962). McMullan & Craven (1989;hereafter MC) have determined the structure from neutron diffraction data collected at 15, 60 and 123 K and carried out a thermal-vibrational analysis at each temperature. In the crystal structure of 1-methyluracil, the molecules are very efficiently packed to form sheets which lie in the crystallographic mirror planes z --0, ~ in the space group Ibam.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of compounds incorporating the pyrimidine-2,6-dione fragment has revealed that the bond lengths within this moiety assume different values in different derivatives, depending on the chemical environments resulting from the nature of the substituents (Everaert, Peeters, Blaton & De Ranter, 1990;McMullan& Craven, 1989;E1 Couhen, Courseille, Precigoux, Constant & Lhomme, 1983;Warin, Lobry, Baert, Bernier & Henichart, 1979;St,etlhandske, Bruins Slot & Beurskens, 1985). In (4), the C(7)---N(3) bond is significantly shorter than the C(7)---N(2) bond (Table 2), which indicates extensive 7r delocalization along the chain…”
Section: C16h20n604smentioning
confidence: 99%